2010
DOI: 10.1016/j.jacc.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Mortality in Patients With Cardiovascular Disease

Abstract: In patients with cardiovascular disease, light to moderate alcohol consumption (5 to 25 g/day) was significantly associated with a lower incidence of cardiovascular and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
4
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(200 citation statements)
references
References 35 publications
12
178
4
6
Order By: Relevance
“…The benefits and problems associated with the consumption of alcohol among the elderly are controversial. Some studies point out to benefits from light consumption regarding mortality (COSTANZO et al, 2010), diminished dementia (SOLFRIZZI et al, 2007, multiple cardiovascular events (RONKSLEY et al, 2011), motor performance and functional capacity (CAWTHON et al, 2007). Disorders arising from excessive alcohol consumption among the elderly are common and is associated with a number of health problems, such as a higher number of falls, mental confusion, depression (O'CONNELL et al, 2003) and poor performance in motor tasks (CAWTHON et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits and problems associated with the consumption of alcohol among the elderly are controversial. Some studies point out to benefits from light consumption regarding mortality (COSTANZO et al, 2010), diminished dementia (SOLFRIZZI et al, 2007, multiple cardiovascular events (RONKSLEY et al, 2011), motor performance and functional capacity (CAWTHON et al, 2007). Disorders arising from excessive alcohol consumption among the elderly are common and is associated with a number of health problems, such as a higher number of falls, mental confusion, depression (O'CONNELL et al, 2003) and poor performance in motor tasks (CAWTHON et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The health effects of drinking depend on the quantity and pattern of alcohol consumption. Although several studies have showed that light to modest alcohol consumption (especially wine or beer) is linked to a decrease in cardiovascular events and total mortality [1,2], some studies indicated that the relationship between alcohol consumption and several cardiovascular diseases is uncertain or negative even at moderate intakes [3][4][5]. Furthermore, excessive alcohol consumption adversely affects human health.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of a national UK AAA screening programme provides a clear opportunity to instigate secondary prevention strategies to prevent the progression of AAA. Alcohol appears to have a dose dependent relationship to ischaemic heart disease, whereby it is protective in moderate doses but harmful in large doses [23][24][25]. The link between alcohol intake and AAA is, however, much less widely reported.…”
Section: Discussionmentioning
confidence: 99%